Working Class Experience: Rethinking the History of Canadian Labour, 1800-1991 - Palmer, Bryan D. (McClelland & Stewart, 1992)
Working Class Experience is a sweeping and sympathetic study of the development of the Canadian working class since 1800. Beginning with a substantial and provocative introduction that discusses the historiography of the Canadian working class, the book goes on to establish a general framework for analysis of what ultimately is a social history of Canada. Dividing the years into seven periods in the evolution of class struggle, it beings each chapter with an assessment of that period's prevailing economic and social context, followed by an examination of the many factors affecting the working class during that period. Written in a colourful and sometimes irreverent style, Working Class Experience focuses on the processes by which working people moved, and were moved, off the land and into the factories and other workplaces during the Industrial and post-Industrial Revolutions in Canada. Drawing on much recent work on contemporary capitalism, Working Class Experience offers a significant explanation of the malaise in current labour and management relations and speculates on its significance for progressive change in Canadian Life. --Publisher's description